Review and Interpretation of Trends in DNA Barcoding - DeSalle, Rob; Goldstein, Paul (Frontiers in Ecology and Evolution, 2019)
Interpretations and analytical practices surrounding DNA barcoding are examined using a compilation of 3,756 papers (as of December 31, 2018) with “DNA Barcode” in the abstract published since 2004. By examining the rise of DNA barcoding in natural history and biodiversity science over this period, we hope to detect the extent to which its purposes, premises, rationale and application have evolved. The number of studies involving identification, taxonomic decisions and the discovery of cryptic species has grown rapidly and appears to have driven much of the publication activity of DNA barcode studies overall. Forensic studies and papers on biological conservation involving DNA barcodes have loosely tracked the ensemble number of studies but appear to have risen sharply in 2017. Although analytical paradigms have diversified, particularly following the growing availability of tools in BoLD, neighbor-joining and graphic (tree-based) criteria for species delimitation remain preeminent. We conclude that the practices and paradigms of DNA barcoding data are likely to persist and, in groups such as Lepidoptera, remain a widely used tool in taxonomic science.